Tantangan Penggunaan Buku Cetak di Era Digital pada Pembelajaran Bahasa Arab - Mawaddah, Syarifah Jasmin; Billah, Miza Almutasya; Nurfitriyana, Nurfitriyana (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose- This research aims to examine the effectiveness and relevance of printed books, as well as the strategies for balancing printed and digital resources and the challenges faced in Arabic language learning in the digital era. And the challenges of using printed books in Arabic language learning in the digital era. Design/Methodology/Approach-  The study employs a qualitative descriptive method using interviews and library research, with books and journal articles as the primary data sources. Interviews were conducted at Institut Agama Islam Negeri Datuk Laksemana Bengkalis. Findings— The results of  the study indicate that students face various challenges in using printed books in Arabic language learning in the digital era. However, printed books remain in use and are considered relevant when balanced with the integration of digital technology. Research Limitation/Implications- The limitations of this study are limited to interviews with students Institut Agama Islam Negeri Datuk Laksemana Bengkalis and the use of written sources, such as journal articles and legal documents, as additional data.